Microbiota regulates bone marrow mesenchymal stem cell lineage differentiation and immunomodulation - E Xiao; Linhai He; Qiong Wu; Junxiang Li; Yang He; Lu Zhao; Shuo Chen; Jingang An; Yansong Liu; Chider Chen; Yi Zhang (Stem Cell Research & Therapy, 2017)
Abstract Health is dependent on the homeostasis of both inner and external microenvironments. The microbiota as the external microenvironment plays a critical role in regulation of several organ systems in mammals. However, it is unclear whether the microbiota regulates homeostasis of the skeletal system and bone marrow mesenchymal stem cells (BMMSCs). Here, using a well-established germ-free (GF) mouse model, we show that the microbiota significantly alters the stemness of BMMSCs in comparison to specific-pathogen-free (SPF)-derived BMMSCs. Colonization of GF mice with SPF microbiota (conventionalized (ConvD)) normalizes the proliferation and differentiation abilities of BMMSCs. On the other hand, normal microbiota is required to maintain immunomodulatory properties of BMMSCs through induction of activated T-cell apoptosis and cytokine secretion. GF-derived BMMSCs lose the capacity to ameliorate disease phenotypes in dextran sulfate sodium-induced experimental colitis mice. Mechanistically, single-cell RNA-sequencing analysis shows that ConvD BMMSCs have a similar gene expression pattern to SPF-derived BMMSCs, which have a distinct gene distribution from GF-derived BMMSCs.